"Serpentino della Valmalenco" (Central Alps, Northern Italy): A green dimension stone with outstanding properties. (March 2022) - Cavallo, Alessandro
Abstract: the " Serpentino della Valmalenco ", a group of serpentinite varieties, was quarried and used as a dimension and building stone since the XI century, especially in thin slabs for roof covering. The extractive activity initially took place in underground, moving to open pit quarries in the 20th century. It is currently a widely used and appreciated material on the international market, commercialized in several commercial varieties and processed in many ways. The schistose varieties are characterized by a marked mylonitic foliation, which confers excellent attitude to splitting, whereas the "massive" ones are suitable for paving and cladding. The rocks are made up of abundant antigorite, with minor olivine, clinopyroxene, chlorite and magnetite. The excellent values in compressive and flexural strength, as well as the extremely low porosity, are documented by ultra-centenarian roofs and high-stress applications. The significant historical heritage, represented by underground quarries, historic buildings, and trade routes, deserves to be enhanced with the development of geotouristic routes. At the same time, the peculiar chemical, mineralogical and microstructural characteristics of the material open the horizons to new applications. Highlights: Roof slabs trade dating back to the 11th century. Schistose and "massive" varieties with a global market. History and tradition: from active quarries to geotouristic routes. Space for circular economy: innovative ideas for waste recovery.